IMPLEMENTASI PEMBELAJARAN AKTIF (ACTIVE LEARNING) UNTUK MENINGKATKAN KOMPETENSI SPIRITUAL DAN SOSIAL SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA - Yayat Sudrajat (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research is inspired by teachers’ current state which is demanded to have competencies in designing effective and meaningful learning, fun, organizing the learning well, choosing the right approach or learning model so students can actively learn and create a student-centered learning. It is expected to enhance the competence of social attitudes, spiritual attitudes, knowledge, and skills. The enhancement itself can be seen through the results of the learning assessment. This study intends to see the implementation of active learning through the application of Pancasila and Civics education models at SMK Negeri Pancatengah which can improve students' spiritual and social competences. This research is based on Piaget and Vygotsky’s constructivist learning theory, Active Learning from Silberman (2014:9), Active Learning from Warsono (2013:5), Attitude theory from Mar’at (1982:13), the concept of social and spiritual attitudes from Mulyasa (2015:17). The approach used in this research is qualitative with descriptive method. The process of collecting data is conducted through observation, interview, documentation study, and literature study. Meanwhile, the stages of data analysis are in the form of data collection, data presentation, data reduction, and data verification/conclusion. The results of the study found by the researcher stated that the teacher has understood the concept and implementation of active learning by practicing it in the application of some active learning models such as problem-based learning, Inquiry Learning, Discovery Learning, and Project-Based Learning. Active learning plan has been carried out thoroughly. In the implementation of active learning, the teacher has demonstrated the step of applying the active learning model systematically. The implementation of the learning assessment has shown objective results in line with the improvement of students’ competencies of spiritual and social attitudes. In its implementation, the supports and challenges are not very influential so the implementation of active learning shows the success of improvement towards the competence of students' attitude. Recommendations from this study include: First, The school continually provides moral and material support, especially in terms of improving teachers' understanding of the concepts and principles of active learning, Second, The teacher is expected to be aware of models and learning strategies by growing the desire to be a learner teacher. Third, The school continues to cultivate the application of learning models and provide flexibility to teachers and students for learning innovation. Fourth: Encourage teachers to conduct classroom research or other research.